FinTech AI, ML & BlockChain Start-up Transformed Financial Service and Financial Inclusion of SMEs/MSMEs in India: To Achieve Sustainable Economic Growth (UDBODHA Enlightenment of facts : ISBN - 978-93-94893-02-3, 2022)
Purpose: The pandemic has accelerated the adoption of technology in financial services, driving innovation in day-to-day financial transactions through AI, ML, Data Science, Blockchain, Web 3.0, and 5G technologies. Startups now have opportunities for re-skilling and promoting sustainable business practices among Micro, Small, and Medium-sized Enterprises (MSMEs) and communities. United Payments Interface (UPI), Fastag, Buy Now Pay Later (BNPL), and Bharat Interface for Money (BHIM), along with initiatives like StartupIndia and Digital India, offer avenues for decent work and economic growth to achieve Sustainable Development Goals (SDGs). India ranks 62nd out of 74 emerging countries in the Inclusive Development Index (IDI) compiled by the World Economic Forum (WEF). Financial Technology (FinTech) startups leverage software, Application Programming Interfaces (APIs), QR codes, Distributed Ledger Technology, IoT, and algorithms to collaborate with the banking industry in transforming products, people, players, and policy frameworks. FinTech can provide direct or formal finance to MSMEs through Jan Dhan-Aadhar-Mobile (JAM), B2B payments, and Peer-to-Peer (P2P) platforms, reducing reliance on indirect finance while aligning with technology trends. Industry 4.0 has further facilitated financial inclusion.Design/Methodology/Approach: This study employs a descriptive approach and utilizes secondary data collected from sources including the Reserve Bank of India (RBI), the Institute for Financial and Banking Excellence (IFBE), and government websites. The analysis leads to the development of the FinTech 4P Model within the ABCD Listing Framework.Findings and Results: Digital India initiatives, along with startup schemes and 100% regulatory support from the RBI, have created a favorable environment for the growth of FinTech in the financial services sector.